2017
DOI: 10.1515/aee-2017-0063
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and time domain characteristics of digital control of electric vehicle in-wheel drives

Abstract: Abstract:In-wheel electric drives are promising as actuators in active safety systems of electric and hybrid vehicles. This new function requires dedicated control algorithms, making it essential to deliver models that reflect better the wheel-torque control dynamics of electric drives. The timing of digital control events, whose importance is stressed in current research, still lacks an analytical description allowing for modeling its influence on control system dynamics. In this paper, authors investigate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…The trasmission gear ratio is indicated in Table 5. To account for the electric motor torque regulator dynamics, a first order time lag was introduced in the model [3,18]. The power losses of each motor, P loss;ij , are defined as functions of motor torque, C ij , and motor speed, X ij , as the difference between the input power, P in , and the output power, P out :…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The trasmission gear ratio is indicated in Table 5. To account for the electric motor torque regulator dynamics, a first order time lag was introduced in the model [3,18]. The power losses of each motor, P loss;ij , are defined as functions of motor torque, C ij , and motor speed, X ij , as the difference between the input power, P in , and the output power, P out :…”
Section: Resultsmentioning
confidence: 99%
“…Recent years have seen an increasingly large interest in vehicle electrification and Advanced Driver Assistance Systems (ADAS), both deemed key features for the future of private transportation. From an engineering point of view, vehicle electrification has opened plenty of possibilities in terms of powertrain layouts and exploitable features, some of which are simply impossible to achieve with a traditional architecture [1][2][3]. A very interesting layout for electric vehicles consists of either four motors (one per wheel) or two motors on the same axle, i.e., one on the left wheel and one on the right wheel of the axle [4].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the selection of the discretization technique is the key factor for constructing resonant controllers [31]. In many simulations, the discretized controllers exhibited nearly identical frequency responses to those of the continuoustime controller [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…In transport engineering, such companies as FordMotors, GeneralMotors, Chrysler, Reno, Fiat, Pegeot, Volkswagen, TokyoElectricPowerCo, AseaBrownBoveri and others are engaged in the development of electric drives used in cars and their electrical equipment. [3,4,5]. An example is the development of Volkswagen.…”
mentioning
confidence: 99%